2010
DOI: 10.5194/acp-10-383-2010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of aerosols on polarized sky radiance: model development, validation, and applications

Abstract: Abstract. Although solar radiation initially is unpolarized when entering the Earth's atmosphere, it is polarized by scattering processes with molecules, water droplets, ice crystals, and aerosols. Hence, measurements of the polarization state of radiation can be used to improve remote sensing of aerosols and clouds. The analysis of polarized radiance measurements requires an accurate radiative transfer model. To this end, a new efficient and flexible threedimensional Monte Carlo code to compute polarized radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 37 publications
0
69
0
Order By: Relevance
“…It is required, for example, for closure experiments (consistency checks between different measurement methods involving an aerosol model, e.g., Wiegner et al, 2009;Gasteiger et al, 2011b;Müller et al, 2012;Bell et al, 2013;Ma et al, 2014;Zieger et al, 2014;Düsing et al, 2018), radiative transfer studies (e.g., Otto et al, 2009;Emde et al, 2010), the inversion of remote-sensing measurements (e.g., Dubovik et al, 2006;Gasteiger et al, 2011a;Müller et al, 2016), the inversion of in situ data (e.g., Weinzierl et al, 2009;Szymanski et al, 2009;Kassianov et al, 2014), aerosol layer visibility simulations (e.g., Weinzierl et al, 2012), dynamic aerosol transport models (e.g., Heinold et al, 2007;Balzarini et al, 2015), aerosol characterization (e.g., Gasteiger et al, 2017;Che et al, 2018;Zhuang et al, 2018), and solar energy (e.g., Polo et al, 2016;Kosmopoulos et al, 2017).…”
Section: Applicationsmentioning
confidence: 99%
“…It is required, for example, for closure experiments (consistency checks between different measurement methods involving an aerosol model, e.g., Wiegner et al, 2009;Gasteiger et al, 2011b;Müller et al, 2012;Bell et al, 2013;Ma et al, 2014;Zieger et al, 2014;Düsing et al, 2018), radiative transfer studies (e.g., Otto et al, 2009;Emde et al, 2010), the inversion of remote-sensing measurements (e.g., Dubovik et al, 2006;Gasteiger et al, 2011a;Müller et al, 2016), the inversion of in situ data (e.g., Weinzierl et al, 2009;Szymanski et al, 2009;Kassianov et al, 2014), aerosol layer visibility simulations (e.g., Weinzierl et al, 2012), dynamic aerosol transport models (e.g., Heinold et al, 2007;Balzarini et al, 2015), aerosol characterization (e.g., Gasteiger et al, 2017;Che et al, 2018;Zhuang et al, 2018), and solar energy (e.g., Polo et al, 2016;Kosmopoulos et al, 2017).…”
Section: Applicationsmentioning
confidence: 99%
“…Although Rayleigh scattering is known to cause high polarization of sky radiance, multiple scattering, and aerosol scattering tend to lower the polarization. Emde et al (2010) found that the maximal sky polarization decreases to ∼15% for an atmosphere containing water soluble aerosol and to ∼12% for an atmosphere containing sea salt aerosol. Since both of these aerosol types are prevalent in the area of Rosh HaNikra (e.g., Bardouki et al, 2003), we can assume that such aerosol contribute to the relatively low maximal sky polarization observed in the current study.…”
Section: Two-dimensional Maps Of Dolp and Aolpmentioning
confidence: 99%
“…However, the intensity of light reflected off of the ocean is lower than the intensity of light propagating from the sky into the cave. Furthermore, as mentioned above, the presence of marine aerosols may cause a decrease in sky polarization (Emde et al, 2010). Therefore, the proximity of the cave to the ocean may or may not produce a net increase in polarization within the cave.…”
Section: Mean Dolp and Aolp For Each Section Of The Imagementioning
confidence: 99%
“…BMC algorithms generally treat the sampling of propagation directions by omitting the radiation's polarisation state and correcting subsequently for the bias introduced (Collins et al 1972 and works thereafter; e.g. Emde et al 2010;Gay et al 2010;Oikarinen 2001). As shown below, that approach may fail to render accurate solutions in conditions for which the scattering directions of the photons are strongly influenced by their polarisation states.…”
Section: The Bmc Algorithmmentioning
confidence: 99%